Tomada de decisões do enfermeiro face a assistência ao paciente - Almeida, Maria Helia de (1976)
In this report special attention is drawn to the sionss as a processs made by the chief nurse of an internment unit» □ne tries to distinguish the limits faund by this nurse9 within the system of organisation of the institution9 of his relations™ hip with the executive team and the use of knowledge in administratíon? technical education of how to take care of the patieot and how to coor™ denate the assistance to the patiento * His opinion regarding priority assignments and executed assignments is emphasized, This report is basêd on informations collected through in vestigations 'effected among chief nurses of ari internmerit unit of a training hospitalo Finally a comparative analysis is made of the problema raised and the informations obtained,